Intracellular Multiplication and Virulence of Shigella flexneri Auxotrophic Mutants - Cersini, Antonella (American Society for Microbiology, 1998)
We have constructed and analyzed a group of Shigella flexneri 5 auxotrophic mutants. The wild-type strain M90T was mutagenized in genes encoding enzymes involved in the synthesis of (i) aromatic amino acids, (ii) nucleotides, and (iii) diaminopimelic acid. In this way, strains with single (aroB, aroC, aroD, purE, thyA, and dapB) and double (purE aroB, purE aroC, purE aroD, purE thyA) mutations were obtained. Although the Aro mutants had the same nutritional requirements when grown in laboratory media, they showed different degrees of virulence in vitro and in vivo. The aroB mutant was not significantly attenuated, whereas both the aroC and aroD strains were severely attenuated. p-Aminobenzoic acid (PABA) appeared to be the main requirement for the Aro mutants’ growth in tissue culture. Concerning nucleotides, thymine reduced the pathogenicity, whereas adenine did not. However, when combined with another virulence-affecting mutation, adenine auxotrophy appeared to potentiate that mutation’s effects. Consequently, the association of either the purE and aroC or the purE and aroD mutations had a great effect on virulence as measured by the Sereny test, whereas the purE aroB double mutation appeared to have only a small effect. All mutants except the dapB strain seemed to move within a Caco-2 cell monolayer after 3 h of infection. Nevertheless, the auxotrophs showing a high intracellular generation time were negative in the plaque assay. Knowledge of each mutation’s role in attenuating Shigella strains will provide useful tools in designing vaccine candidates.